Eco-City Projects: Incorporating Sustainability Requirements during Pre-Project Planning. Issue 1 (2nd January 2017) - Mneimneh, Farah; Srour, Issam; Kaysi, Isam; Harb, Mona
ABSTRACT: International standards exist for evaluating building or neighborhood sustainability. Nonetheless, they are still not available for large-scale developments. Of special interest to practitioners is how to ensure that sustainability requirements of large-scale projects are well integrated in a master plan. This paper provides design managers of new eco-cities with a framework to integrate sustainability in the pre-project planning phase. A case study of a planned eco-city is investigated to delineate its pre-project planning practices, compare them to the proposed framework, and infer lessons learned. The case study highlights the importance of regular interactions between business planners and master planners to incorporate sustainability requirements at early planning phases.